Upaya Menghilangkan Rasa Takut yang membayangi Perempuan Korban KDRT - Nisa Hutasoit; Bengkel Ginting (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
The high rate of domestic violence can have a negative impact on the health of the victim's wife. These effects include eating and sleeping disorders, anxiety, fatigue, disability, post-traumatic stress, which are long-term responses. When looking at the mental health of women victims of domestic violence, most of the victims perceive their own failure as a wife, failure as a mother who can be an example for their children, and the shame caused by others in relation to the perception of violence experienced by the victim. . Regarding the victim's ability to adapt to pressure, stress, and anxiety, victims of domestic violence cannot adapt to stress, stress and anxiety overall because they worry about their children in the event of a divorce, and victims also experience anxiety when: The sound of throwing goods and the sound of slamming doors frightens the victim. The self-image of victims of domestic violence in general tends to be negative, namely guilt, shame, shame, fear of being exposed to domestic violence, and feeling that the victim is the cause of her husband's anger. The method used by the author uses the case work intervention model proposed by Zastrow in the book Rukmnto Adi, Isbandi (2013). Overcoming client problems with social functions involving family and closest relatives.